Toxicological, genotoxic and antioxidant potential of Pyrostegia venusta (Bioscience Journal, 2019)
Pyrostegia venusta is usually found in the secondary growth of the Atlantic forests, and in the Brazilian Savanna. Flowers and leaves of this plant are used in folk remedies for treating a wide variety of healthy conditions, this way is important evaluate its safety and antioxidant potential for this applications. For this, was made a ethanolic extract from its flowers and analyzed with toxicological, genotoxicity and antioxidant tests, the toxicological analysis was made by reproductive toxicity in rats and clatogenicity/aneugenicity in human lymphocytes. The genotoxicity was studied by micronucleus test mice bone marrow. The antimutagenic test in root cells of Allium cepa, the antioxidant assays used was DPPH, FRAP, Lipid Perxidation and REM, beyond of that the extract was analyzed in HPLC showing the profile of its compounds. The toxicological analysis showed that P. venusta has no negative significant effect on reproductive and cellular level. The micronucleus test in mouse bone marrow, the extract protected cells from cyclophosphamide, mutagenic compound, in a similar way. The A. cepa test showed that the extract reduced chromosomal disorders formations. The antioxidant activity of extract was significant, except in REM test. The phytochemical analysis showed the presence of flavonoids compounds. P. venusta extract does not present reproductive toxicity and genotoxic effects. However, the extract of this species showed antigenotoxic and antioxidant potential, possibly due to the different flavonoid compounds present in its extract.